Perancangan Sistem Informasi Biro Perjalanan Wisata Di PT. Alya@NET Tours And Travel Berbasis Web - Nela Sandiana Liga Nela; Rengga Herdiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
A travel agency is a travel company that sells travel plans and sells other travel-related products directly to the public. The company makes and designs various kinds of tourism products from various existing tourism services, into an attractive tour package for tourists. PT. Alya@NET Tours And Travel is here to offer travel management services, both private and corporate. PT. Alya@NET Tours And Travel always strives to meet needs from small to big things, from planning to implementing tours. Problems faced by PT. Alya@NET Tours And Travel at this time is difficult to provide the latest information regarding the availability of travel tickets. Which results in delays in booking travel tickets that are still available. With the existing problems, this research focuses on designing a travel agency application for PT. Alya@NET Tours And Travel is web based. By using the waterfall method.